Silver nanoparticles stabilized in hydroalcoholic extract of mentha piperita as an adjuvant in the treatment of depression (Research, Society and Development, 2022)
Introduction: Silver nanoparticles are increasingly relevant in medical practice. It is noteworthy that plant-based metal nanoparticle synthesis is an emerging approach in nanoparticle synthesis. Objective: To develop silver nanoparticles stabilized in the hydroalcoholic extract of Mentha Piperita L. for the adjuvant treatment of depression. Methodology: In the synthesis of nanoparticles in a solution, 25 mL of silver nitrate (1.0 mmol/L) and 75 mL of sodium borohydride (2.0 mmol/L) were used. These two substances were mixed at room temperature under magnetic stirring. Another solution used 100 mL of silver nitrate (1.0 mmol/L) until boiling temperature was reached and 5 mL of sodium citrate (1%) was added under magnetic stirring. The hydroalcoholic dry extract of mint was obtained from dried leaves and 70% alcohol. Results: The isolated analyzes of the solutions showed absorbance peaks from 266 to 420 nm. When mixing the solutions, it was noted that in the presence of sodium borohydride the maximum absorbance peaks were higher. Conclusion: For both solutions (with citrate/borohydride) the formation of silver nanoparticles was identified, indicating that the mint extract is able to stabilize AgNps.